Developed Correlations for Prediction of The Enthalpies of Saturated Vapor Liquid Coexisting Phases - Abdullah, Mahmoud Omar; Al-Jiboury, Khalid Farhod Chasib (Nahrain University College of Engineering Journal, 2010)
In this study a new criteria is adopted by the use of Rectilinear Diameter principle to express the saturated vapor and liquid enthalpies at the coexisting phases for pure substances and mixtures, this requires another relation that used to calculate enthalpies of vaporization at the corresponding temperatures.The relationships between saturated vapor enthalpy, saturated liquid enthalpy and pressure are investigated for many pure substances. These investigations show that the saturated vapor and liquid enthalpies cannot be described by pressure as a simple general relation. New simple correlations are developedfor pure substances and mixtures. These correlations are based on the principle of Rectilinear Diameter depending on the law of corresponding states, where DH is introduced as a dimensionless term including the average reduced saturated enthalpies. The relations developed are